2017
DOI: 10.1016/j.apgeochem.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distributions of Pu and radiocesium isotopes in sediments from Lake Inba after the Fukushima Daiichi Nuclear Power Plant accident: Source identification and accumulation

Abstract: Radiocesium isotopes were released into the environment in the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, which resulted from the massive Tohoku earthquake in March 2011. Lake Inba is located in Chiba Prefecture about 200 km from the FDNPP site and the lake was contaminated by radioactivity from the accident. The present work was carried out in order to investigate the vertical distributions and accumulations of radiocesium and Pu in sediment cores collected during 2011-2015, and to study the migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The first local 137 Cs source detected in Japan was attributed to the atomic bomb peak in 1945 in the Nagasaki area (Mahara and Kudo, 1995). The peak associated with the atmospheric nuclear tests in 1963 was then largely recorded across the entire Japanese peninsula (e.g., Lu and Matsumoto, 2009;Hosono et al, 2016) whereas the fallout associated with the Fukushima accident was mainly identified in the vicinity of the Fukushima NPP, in particular in lacustrine sediments of the Miyagi, Fukushima and Ibaraki prefectures (Cao et al, 2017;Jaegler et al, 2019;Minoura et al, 2014), as well as in sediment samples collected along the Pacific coast off the Fukushima prefecture (e.g., Black and Buesseler, 2014) -(Fig. 4).…”
Section: General Patterns Of 137 Cs Falloutmentioning
confidence: 99%
“…The first local 137 Cs source detected in Japan was attributed to the atomic bomb peak in 1945 in the Nagasaki area (Mahara and Kudo, 1995). The peak associated with the atmospheric nuclear tests in 1963 was then largely recorded across the entire Japanese peninsula (e.g., Lu and Matsumoto, 2009;Hosono et al, 2016) whereas the fallout associated with the Fukushima accident was mainly identified in the vicinity of the Fukushima NPP, in particular in lacustrine sediments of the Miyagi, Fukushima and Ibaraki prefectures (Cao et al, 2017;Jaegler et al, 2019;Minoura et al, 2014), as well as in sediment samples collected along the Pacific coast off the Fukushima prefecture (e.g., Black and Buesseler, 2014) -(Fig. 4).…”
Section: General Patterns Of 137 Cs Falloutmentioning
confidence: 99%
“…The 239+240 Pu activities in surface sediments of river basins in southern China was much higher than that in surface soils, and this might be associated with the result of multiple factors, including (1) the organic matter contents and particle sizes of surface sediments of river basins, (2) the variable climatic conditions (rainfall, humidity, wind, etc. ), for example, wind and rain have competing effects on the amounts of resuspended plutonium-containing material collected, , (3) estuary experiences (such as river runoff, tide bores, currents, and anthropogenic activities (dam-building, oil exploration, nuclear power plants)), and (4) the material composition of the surface sediments.…”
Section: Resultsmentioning
confidence: 99%
“…The idea is constructed by assuming that the catchment-derived 137 Cs has a significant contribution to the total 137 Cs inventories in the lake sediment cores 13) and the vertical profile is time-dependent. 14) The relatively easier method of estimation was performed by using 137 Cs soil to lake sediment ratio to estimate the 137 Cs initial accumulation and flushing in the sediment of the lake just after the accident, however, it needs more investigation regarding its robustness. 15) In the present study, we examined the 137 Cs distributions and 137 Cs soil to lake sediment ratio for investigating the radiocesium migration.…”
Section: Introductionmentioning
confidence: 99%